2012
DOI: 10.1099/ijs.0.037218-0
|View full text |Cite
|
Sign up to set email alerts
|

Naumannella halotolerans gen. nov., sp. nov., a Gram-positive coccus of the family Propionibacteriaceae isolated from a pharmaceutical clean room and from food

Abstract: Four Gram-stain-positive, aerobic bacterial strains isolated from a pharmaceutical clean room (strain WS4616T), a dessert milk product (strain WS4617) and from raw milk (strains WS4623 and WS4624) were characterized using a polyphasic approach. Phylogenetic analyses based on 16S rRNA and recA gene sequences showed that they formed a distinct lineage within the family Propionibacteriaceae . Similarity values between 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Several research projects, therefore, developed an identification technology based on Fourier-transform infrared (FT-IR) spectroscopy, which fulfilled the following criteria: ease of use, fast and reliable results, high sample throughput and low costs as no consumables are required. During the course of many studies in our laboratory, thousands of micro-organisms have been isolated from industrial environments and identified by this method and novel species have been discovered (Bleicher et al , 2010; Rieser et al , 2012; Schmidt et al , 2009, 2012).…”
mentioning
confidence: 99%
“…Several research projects, therefore, developed an identification technology based on Fourier-transform infrared (FT-IR) spectroscopy, which fulfilled the following criteria: ease of use, fast and reliable results, high sample throughput and low costs as no consumables are required. During the course of many studies in our laboratory, thousands of micro-organisms have been isolated from industrial environments and identified by this method and novel species have been discovered (Bleicher et al , 2010; Rieser et al , 2012; Schmidt et al , 2009, 2012).…”
mentioning
confidence: 99%